Nitrogen addition promotes early-stage and inhibits late-stage decomposition of fine roots in Pinus massoniana plantation - Wang, Lijun; Shen, Yafei; Cheng, Ruimei; Xiao, Wenfa; Zeng, Lixiong; Sun, Pengfei; Chen, Tian; Zhang, Meng (Frontiers in Plant Science, 2022)
Increasing atmospheric nitrogen (N) deposition has a profound impact on the ecosystem functions and processes. Fine root decomposition is an important pathway for the reentry of nutrients into the soil. However, the effect of N addition on root decomposition and its potential mechanism is not well understood with respect to root branch orders. In this study, we conducted a 30-month decomposition experiment of fine roots under different concentrations of N addition treatments (0, 30, 60, and 90 kg N ha-1 year-1, respectively) in a typical Pinus massoniana plantation in the Three Gorges Reservoir Area of China. In the early stage of decomposition (0‒18 months), N addition at all concentrations promoted the decomposition of fine roots and the release of lignin, C, N, and P. In the late stage of decomposition (18‒30 months), high N addition inhibited the decomposition of fine root and the release of lignin, C, N, and the activities of lignin-degrading enzyme (peroxidase and polyphenol oxidase). The decomposition constant (k) was significantly correlated with the initial chemical quality of the fine roots and lignin-degrading enzyme activities. The higher-order (order 3–4 and order 5–6) fine roots decomposed faster than lower-order (order 1–2) fine roots due to higher initial cellulose, starch, sugar, C concentrations and higher C/N, C/P, lignin/N ratios and lower N, P concentrations. In addition, low N treatments decreased soil organic matter content, whereas high N treatment had the opposite effect. All the N treatments reduced soil pH and P content, indicating that increased N deposition may led to soil acidification and P limitation. Our findings indicated that the effect of N addition on decomposition varied with the decomposition stages. The decomposition difference between the lower-order and higher-order fine roots were controlled strongly by the initial chemical quality of the fine roots. This study provides new insights into understanding and predicting possible changes in plant root decomposition and soil properties in the future atmospheric N deposition increase scenarios.